Research trends in the development of generic skills - Ramírez-Ramírez, Diana Marleny; Agudelo-Ceballos, Erica; Jimenez Garcia, Jesus Alberto; Valencia-Arias, Alejandro; Cardona-Acevedo, Sebastián; Valencia, Jackeline; Ynoquio, Erick (Frontiers in Education, 2025)
IntroductionGeneric skills, also known as soft skills, are transversal competencies essential for professional success, encompassing cognitive, social, and emotional abilities. Despite their relevance, leadership behaviors during the implementation of educational methodologies reveal gaps in understanding how to effectively develop these skills in specific sectors.MethodsA bibliometric analysis was conducted following the PRISMA 2020 protocol to identify trends, key contributors, and thematic evolution in research on generic skills. The review synthesized publications from relevant databases, mapping authorship, institutional contributions, and conceptual clusters.ResultsThe analysis indicated a notable growth in research output during 2021 and 2022. Key references included Chan, the journal Studies in Higher Education, and contributions from Australia and the United Kingdom. The thematic focus evolved from “Transferable Skills” toward “Higher Education” and “Engineering Education,” with conceptual clusters such as “General Education,” “Higher Education,” and “Gamification.” Emerging terms like “employability” and “leadership” were identified as central to the discourse.DiscussionFindings highlight the increasing scholarly attention to soft skills in educational contexts, yet also reveal the persistent need to integrate these competencies systematically into teaching and leadership practices. Based on the observed thematic trends, a research agenda is proposed that emphasizes the incorporation of innovative methodologies and emerging technologies to strengthen soft skills development across diverse sectors.